Pengaruh Kepemimpinan Etis dan Kepemimpinan Emosional Atas Niat Berhenti Berkerja di Kantor Dinas Pendidikan Kabupaten Tangerang - Agusriyan Akbar Hidayat; Joel Faruk Sofyan; Wisnu Budi Prasetyo; Dimas Angga Negero (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research examines the influence of ethical and emotional leadership on employee motivation and job performance to measure intentions to leave work. This research is a deductive-quantitative research with a correlation-causal approach, using primary data obtained from an online survey using Google Form. Measurement of all variables used in this research uses a 1-5 Likert scale. The sample for this research is the entire population of Civil Servants at the Tangerang Regency Education Office, totaling 54 people, and using 28 indicators. Confirmatory Factor Analysis (CFA) was carried out to test the quality of the indicators used using pretest data. The data was then processed using the PLS-SEM method to test the hypothesis. The results of this research show that there are 2 related hypotheses, namely the relationship between emotional leadership and employee motivation and the relationship between employee motivation and job performance. Meanwhile, there are 4 hypotheses that have no effect, namely the relationship between ethical leadership and employee motivation, the relationship between ethical leadership and job performance, the relationship between emotional leadership and job performance, and the relationship between job performance and intention to leave work. It can be concluded that none of the Civil Servants intend to stop working, but instead motivate themselves to improve their performance to get more results, and leaders do not have a direct influence on motivation, work performance, and intention to stop working.